The Influence of Digital Media-Based Problem Based Learning Model on Student Motivation and Learning Outcomes in Integrated Social Sciences Courses - Siti Aidilia Azzahra; Shinta Jouito Samosir; Martha Putri Grasya Banurea; Destri Rosmailin Sitanggang (International journal of technology and education research, 2026)
The development of digital technology is driving changes in the learning process in higher education, including in the Integrated Social Studies course. One learning model considered capable of increasing student engagement in the learning process is Problem-Based Learning (PBL). This study aims to analyze the effect of implementing a digital media-based Problem-Based Learning model on student motivation and learning outcomes in an Integrated Social Studies course. The study used a quantitative approach with a survey method. The study subjects consisted of 50 students taking the Integrated Social Studies course. Data collection was conducted by distributing a questionnaire using a Likert scale consisting of 20 statements regarding the implementation of the digital media-based PBL model, learning motivation, and student learning outcomes. Data were analyzed using quantitative descriptive analysis techniques by calculating the percentage of respondents' answers. The results showed that the majority of students responded positively to the implementation of the digital media-based Problem-Based Learning model. Students assessed that problem-based learning improved participation in discussions, critical thinking skills, problem-solving abilities, and understanding of Integrated Social Studies material. Furthermore, the use of digital media facilitated access to information, supported collaboration, and increased student engagement in learning activities. In terms of learning motivation, students demonstrated increased interest, enthusiasm, and active participation during lectures. Meanwhile, in terms of learning outcomes, students found it easier to understand the material, complete assignments, and connect social studies concepts to real-life problems. The findings of this study indicate that the implementation of a digital media-based problem-based learning model positively impacted student motivation and learning outcomes in Integrated Social Studies courses. Therefore, this learning model can be used as an alternative, innovative learning strategy that can support improving the quality of the learning process in higher education